The Representation of Orientation Semantics in Visual Sensory Memory - Jingjing Hu; Xutao Zheng; Haokui Xu (Behavioral Sciences)
Visual sensory memory constructs representations of the physical information of visual objects. However, few studies have investigated whether abstract information, such as semantic information, is also involved in these representations. This study utilized a masking technique combined with the partial report paradigm to examine whether visual sensory memory representation contains semantic information. Here, we regarded the concept of orientation carried by the visual stimulus as semantic information. In three experiments, participants were asked to remember the orientation of arrows. Visual stimuli with orientation information (triangles, rectangles, and Chinese characters) and without orientation information (circles, squares, and different Chinese characters) were used as masks. The results showed that memory performance was worse when masks contained orientation information compared to when they did not, as similar orientation semantic information between masks and targets created visual representation conflicts. These findings suggest that visual sensory memory representation includes the semantic information of orientation.